Direct energy conversion technologies - Singal, R. K.; Tabatabaian, Mehrzad (Mercury Learning & Information, 2020)
This book is designed for students and professionals who specialize in energy technologies and power plant engineering. It covers the mathematics and physics of both current conversion, such as solar cells, fuel cells, MHD, thermoelectric, and thermionic power generation, but also discusses emerging conversion technologies such as solar thermal, nuclear fusion, and hydrogen energy. Written in simple language, illustrated by diagrams, mathematical analysis.
Keywords: Direct energy conversion.; Solar cells.; Solar energy.; elektronické knihy; electronic books